2013
DOI: 10.1161/strokeaha.113.002465
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Hemorrhagic Stroke

Abstract: Background and Purpose-Several studies have assessed the possible increased risk of hemorrhagic stroke in migraineurs, drawing differing conclusions. No meta-analysis on the topic has been published to date. Methods-Multiple electronic databases (MEDLINE, EMBASE, Science Citation Index, and the Cochrane Library) were systematically searched up to March 2013 for studies dealing with migraine and hemorrhagic stroke. We selected casecontrol and cohort studies with a clear definition of the diagnostic criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
6
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 31 publications
5
114
6
5
Order By: Relevance
“…Although the results of individual studies were conflicting, a recent meta-analysis showed that migraine is associated with a 1.48-fold increase in the risk of hemorrhagic stroke, including subarachnoid hemorrhage. RR was not significant higher for MA group, but only for women and for age \45 years, regardless of M subtype [11]. In another study, MA has been associated with HS, and risk was stronger in the subset of women with fatal HS and \55 years of age [12].…”
Section: Epidemiological Datamentioning
confidence: 84%
“…Although the results of individual studies were conflicting, a recent meta-analysis showed that migraine is associated with a 1.48-fold increase in the risk of hemorrhagic stroke, including subarachnoid hemorrhage. RR was not significant higher for MA group, but only for women and for age \45 years, regardless of M subtype [11]. In another study, MA has been associated with HS, and risk was stronger in the subset of women with fatal HS and \55 years of age [12].…”
Section: Epidemiological Datamentioning
confidence: 84%
“…While an association between migraine and stroke has not been confirmed in migraine-without-aura patients, 97 the risk of both ischemic and hemorrhagic 98 stroke is two to three times higher in migraine-with-aura patients. There may, however, be other more profound vascular risks present in these patients who were not accounted for in the studies.…”
Section: Migraine As Risk Factor For Strokementioning
confidence: 98%
“…[11] In addition, there are several published reports suggesting that migraine is a risk factor for stroke. [7,10,17] On the other hand, there are studies that did not demonstrate that migraine was a risk factor for cardiovascular events. Liman et al indicated that there was no significant difference in CAIMT and peripheral arterial tonometry (PAT) ratio in female patients with migraine with aura.…”
Section: Discussionmentioning
confidence: 99%